Coupling between tolerance and resistance for two related Eimeria parasite species. Issue 24 (12th November 2020) - Balard, Alice; Jarquín‐Díaz, Víctor Hugo; Jost, Jenny; Mittné, Vivian; Böhning, Francisca; Ďureje, Ľudovít; Piálek, Jaroslav; Heitlinger, Emanuel
Abstract: Resistance (host capacity to reduce parasite burden) and tolerance (host capacity to reduce impact on its health for a given parasite burden) manifest two different lines of defense. Tolerance can be independent from resistance, traded off against it, or the two can be positively correlated because of redundancy in underlying (immune) processes. We here tested whether this coupling between tolerance and resistance could differ upon infection with closely related parasite species. We tested this in experimental infections with two parasite species of the genus Eimeria . We measured proxies for resistance (the (inverse of) number of parasite transmission stages (oocysts) per gram of feces at the day of maximal shedding) and tolerance (the slope of maximum relative weight loss compared to day of infection on number of oocysts per gram of feces at the day of maximal shedding for each host strain) in four inbred mouse strains and four groups of F1 hybrids belonging to two mouse subspecies, Mus musculus domesticus and Mus musculus musculus . We found a negative correlation between resistance and tolerance against Eimeria falciformis, while the two are uncoupled against Eimeria ferrisi . We conclude that resistance and tolerance against the first parasite species might be traded off, but evolve more independently in different mouse genotypes against the latter. We argue that evolution of the host immune defenses can be studied largely irrespective of parasite isolates if resistance–tolerance coupling is absent or weak ( E. ferrisi ) but host–parasite coevolution is more likely observable and best studied in a system with negatively correlated tolerance and resistance ( E. falciformis ). Abstract : We tested whether closely related parasite species could show different coupling between tolerance and resistance and found a trade‐off between resistance and tolerance to one, Eimeria falciformis, but not to its close relative Eimeria ferrisi . The framework of resistance–tolerance coupling allows to prioritize research questions to be addressed with different parasites: broad questions of relevance for the host species as a whole with parasites showing no coupling, questions of local adaptation and host–parasite co‐evolution with parasites showing coupling.